Modeling of skin tissue heating using the generalized dual phase-lag equation - Majchrzak, E.; Turchan, Ł.; Dziatkiewicz, J. (Archives of Mechanics, 2015)
This paper concerns the numerical modeling of skin tissue heating. To describe the analyzed process the system of three generalized dual phase-lag equations corresponding to the successive layers of the skin: epidermis, dermis and sub-cutaneous region is applied. On the surfaces between the layers the ideal thermal contact is assumed, on the skin surface the Neumann condition describing the external heating of tissue can be accepted, and on the remaining surfaces the no-flux condition is taken into account. Initial temperature of the tissue and the blood is known. The problem is solved using the explicit scheme of finite difference method. In the final part of the paper the results of computations are shown.